'An evolution of a combo': the current state of the North American Sitcom, and its influence from both prior stages of the genre, and contemporary narrative trends through an examination of Schitt's Creek. Issue 2 (3rd July 2021) - Chisholm, Amelia
Abstract: The North American Sitcom is a vastly understudied subject in both televisual and comedic academi a – and yet it best exemplifies the contemporary narrative trend of 'Nicecore'. I have chosen to focus my study upon Schitt's Creek as it epitomizes this phenomenon, whilst also representing what I believe to be the third stage in evolution of the genre. This combines textual and formal trends present in both prior stages, and therefore aids in demonstrating the progression of said evolution. In this article I have analysed the generic features of Schitt's Creek, whilst also assessing the presence of 'Nicecore', and linking both topics to the current political landscape. I believe that this evolutionary trend of the North American Sitcom displays not only its pedagogical implications, but the genre's overall significance.